Studi Penggunaan Antihipertensi Golongan Angiotensin Receptor Blockers Terhadap Pasien Gagal Ginjal Kronik Stadium V di Rumah Sakit Bhayangkara Surabaya - Bura, Ursula Dua Klowe; Hasmono, Didik; Surdijati, Siti; Hartono, Ruddy (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2017)
Chronic renal failure is functional or structural kidney damage for more than 3 (three) months with or without a decrease in the Glomerular Filtration Rate (GFR), manifested as one of the pathological abnormalities or a sign of kidney damage, including blood or urine composition abnormalities or radiology abnormalities. In addition, chronic renal failure is also defined as a condition of GFR value of less than 60 ml / minute / 1.73 m2, for more than 3 (three) months with or without kidney damage. One of the risk factor for chronic renal failure is hypertension. The purpose of antihypertensive administration is to prevent further damage to other organs, and also to reduce blood pressure in patients with chronic renal failure with a target of ≤ 140 mmHg. Angiotensin Receptor Blockers (ARB) is a first-line therapy used to reduce blood pressure so that it can delay kidney damage. The purpose of this study was to determine the pattern of antihypertensive drug use in the ARB class in patients with stage V chronic renal failure at Bhayangkara Hospital in Surabaya which was associated with clinical and laboratory data. The study was conducted observationally with a descriptive research design and retrospective data collection. The results showed that those who met the inclusion criteria were 30 patients using antihypertensive ARB therapy, where the highest number of sexes were 67% male and 33% female, the highest populations at the age of 31-70 years, the highest populations was 90% for ARB use and other antihypertensive drug and a single ARB use of 10 %, the most common combination ofantihypertensive group is ARB and Calsium Channel Blocker (CCB) 41%. The patient’s blood pressure mostly meets the target of ≤ 140 mmHg.